The Mediating Role of Devolved Management on the Influence of Organizational Support on Teacher Creativity - Wahib, Abd (JURNAL AL-TANZIM, 2024)
This research aims to analyze the influence of organizational support on teacher creativity and devolved management as mediating variables at MAN 1 Tuban. The research method used is a quantitative research method using an explanatory research approach with a survey approach. The questionnaire was prepared based on research variables: organizational support, teacher creativity and meaning of work. Research data was taken from 100 teachers who were the sample for this research. Data collection was carried out using random sampling techniques at MAN 1 Tuban. Data analysis in this research uses the Partial Least Square (PLS) approach using Smart PLS software. The research results show that organizational support positively affects employee creativity, which is supported in this research. Organizational support positively impacts devolved management, which is supported in this research. Devolved management positively affects employee creativity, which is supported in this research. Devolved management mediates the positive influence of organizational support on employee creativity, as supported in this research. Due to support from the workplace, recognition and motivation, teachers develop their creative ideas more and feel that their work is essential. Still, employees have more freedom in determining their work.